The Teachers’ Perception Of Using Hangman Games As A Medium In Teaching Vocabulary - Salsabila Ayudi Rizka; Rustam Rustam; Ernita Daulay (Sintaksis : Publikasi Para ahli Bahasa dan Sastra Inggris, 2024)
This research is the qualitative research which aim to know the classroom ambience when using hangman game and to find out the teachers perceive in using hangman game as a medium in teaching vocabulary. This research was conducted on May 2024 in the class of VIII Bilingual B at Al-Azhar Medan Junior High School. Observation and interview were the technique of data collection that used in this research which were carried out directly with 2 teachers who had a long experience in teaching English and used the hangman game as a medium in the vocabulary teaching and learning process. The model of interactive data analysis by Miles and Huberman (1984) is used as the technique of analyzing the data in this research. The findings from the data that have been analyzed show that when using the hangman game, the classroom ambience look supportive, nice, and joyful in supporting the teaching and learning process run well. Both of the teachers have positive and negative perception about using hangman game. Both of the teachers also stated that hangman game is one of appropriate medium to use for the students who want to recall or add their vocabulary. This research provides several useful information, especially for English teacher who need references about tool or media for teaching vocabulary.